Factors that Influence the Level of Medication Adherence in Diabetes Mellitus Patients in Magelang City Hospital - Kemila, Mira; Astyamalia, Suzan (Jurnal Ilmu Kesehatan, 2024)
Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia that occurs due to abnormalities in insulin secretion, insulin action or both. Treatment adherence and low glycemic control are still problems in the majority of DM patients. Non-compliance of type 2 diabetes mellitus patients with treatment will have an impact on expected clinical outcomes, risk of complications, and poor quality of life. Therefore, this study aims to determine the level of compliance of diabetes mellitus patients and analyze the factors that influence it. This study is an analytical study observational with a cross sectional design and carried out at the Internal Medicine Clinic, Magelang City Regional Hospital from December 2023 to January 2024. The sample for this study is diabetes mellitus patients who are taking antidiabetic drugs at the Internal Medicine Clinic, Magelang Regional Hospital. The research instrument is a questionnaire from Morisky Medication Adherence Scale 8-item (MMAS-8). Bivariate data analysis using tests chisquare using SPSS. Effects were considered significant if p < 0.05. Level of adherence to treatment long-term oral antidiabetic in the majority of DM patients are in the Disease Polyclinic In the Magelang City Regional Hospital it is still moderate. This study shows that The amount of medication consumed in a day is factors that have the most influence on level of treatment compliance. Meanwhile, age, gender, occupation and length of suffering DM has no effect on level patient compliance in treatment